Effects of Demographic Factors on Tourism Marketing - Shetty, Niyat; Alok, Divya (SFIMAR Research Review, 2015)
Tourism Industry is one of the fastest growing sectors in Indian Economy. The industry is dynamic and if we see the trend in recent times. Tourist footfalls have increased tremendously by effective marketing and promotion. The best example in this regard is the now famous campaign of Khushboo Gujarat Ki, by the evergreen Amitabh Bachchan. For any sector to grow, it is very important to gauge or foresee the trends in the industry. What are the tourist customer profiles? From where do they get the information about the tourist destinations of Gujarat? Do the tastes and preferences about the destination differ according to the demographic profiles or whether it is common for all people? This paper would throw light on the effects of demographic factors on the tastes and preferences and the source of information used by the tourists to tour Gujarat. At the end of this research paper, the findings would display the mapping between the demographic factors of the tourists and their approach in planning a tour. This paper would be useful to the tourism sector as a whole, to plan out their marketing strategies in targeting the right customer markets. This study is basically based for the tourists visiting Gujarat region. The study can be extended to other states too. This research paper also gives some recommendations on improvements which can be incorporated by the Tourism agencies for the growth of the industry. The growth in Tourism industry depends upon how effective we segment the market and offer customized packages for the respective segment. This paper tries to bridge the gap between these parameters.